2006
DOI: 10.1370/afm.575
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory Reporting of Elder Abuse: Between a Rock and a Hard Place

Abstract: PURPOSE Despite mandated reporting laws that require physicians to report elder abuse, physicians have low rates of reporting. The purpose of this study was to identify physician's perspectives on mandated reporting of elder abuse.METHODS Individual, semistructured interviews were conducted with 20 primary care physicians practicing in a variety of settings and caring for a diverse patient population in the Los Angeles area. Interviewers collected information on physicians' perspectives about factors that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 27 publications
2
61
0
6
Order By: Relevance
“…Although this problem is considered by many authors as rarely reported by health professionals, and despite the fact that they occupy a privileged position to do so, 10,20,24,25 the present study showed a good relationship between the cases in which there was suspicion and reporting. Indeed, of the 78 (61.4%) participants who mentioned to have suspected of at least one event of abuse, 83.3% reported the situation.…”
supporting
confidence: 42%
“…Although this problem is considered by many authors as rarely reported by health professionals, and despite the fact that they occupy a privileged position to do so, 10,20,24,25 the present study showed a good relationship between the cases in which there was suspicion and reporting. Indeed, of the 78 (61.4%) participants who mentioned to have suspected of at least one event of abuse, 83.3% reported the situation.…”
supporting
confidence: 42%
“…1). Same concern about the future life quality of older person was also mentioned in a study conducted in USA (13). Accordingly, there is an apparent clash in legal and ethical responsibilities.…”
Section: Discussionmentioning
confidence: 89%
“…4 This study shows how simple, well-meaning policies can lead to complexity and ambiguity at the point of application that alter the intended consequences.…”
Section: Health Care Policy Studiesmentioning
confidence: 91%